2015
DOI: 10.3233/bme-151522
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography–mass spectrometry analysis of the free fatty acids in serum obtained from patients with Alzheimer’s disease1

Abstract: Abstract. As the worldwide elderly population has grown, the incidence and prevalence of Alzheimer's disease (AD) has steadily increased. The differential lifelong exposure of populations to dietary fatty acids has raised concerns about the potential links between cognitive impairments and nutrition. However, few studies have addressed the levels of free fatty acids (FFAs) in AD patient serum. In this study, gas chromatography-mass spectrometry (GC-MS) was used to determine the levels of 15 serum FFAs in 31 AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…To demonstrate the advantages of the DMPP derivatization method, a comparative study with previously reported methods was established in terms of derivatization conditions, separation capacity, injection time, and detection limits. For methyl esterification, a common derivatization method for FFAs, the GC–MS analysis was time consuming (44 min) and the LOD (0.03–0.08 μg/mL) was much higher than DMPP derivatization (0.86–4.54 pg/mL) . After optimization, the methyl esterification method coupled with ionic liquid was established for the determination of fatty acids, but unfortunately this method was also time consuming (45 min) and the separation capacity was poor .…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the advantages of the DMPP derivatization method, a comparative study with previously reported methods was established in terms of derivatization conditions, separation capacity, injection time, and detection limits. For methyl esterification, a common derivatization method for FFAs, the GC–MS analysis was time consuming (44 min) and the LOD (0.03–0.08 μg/mL) was much higher than DMPP derivatization (0.86–4.54 pg/mL) . After optimization, the methyl esterification method coupled with ionic liquid was established for the determination of fatty acids, but unfortunately this method was also time consuming (45 min) and the separation capacity was poor .…”
Section: Resultsmentioning
confidence: 99%
“…From this, we infer that the decreased Zn 2+ binding capacity of albumin in the presence of FFAs may have significant implications, for both normal and disease-altered physiology. Whilst numerous pathological diseases are associated with elevated levels of free fatty acids, not limited to cardiovascular diseases (including thrombosis), [114][115][116] diabetes, [117][118][119] and neurodegenerative diseases, [120][121][122] FFA levels also fluctuate during periods of intense exercise, fasting and after the consumption of food. [123][124][125] A deeper understanding of the downstream consequences of FFA-mediated Zn 2+ re-distribution is now required to comprehend the wider impact this may have on organismal physiology.…”
Section: Discussionmentioning
confidence: 99%
“…A more complete study analyzed the level of FFAs in the serum of AD patients and found that several of them significantly decreased when compared to the control; the study included 3 saturated fatty acids (C14:0, C16:0, and C18:0) and 6 unsaturated fatty acids (C16:1, C18:1, C18:2, γ-C18:3, C20:2, and C22:6). The serum level of C18:3 was significantly higher in AD patients [ 30 ]. In an elegant study by Martin et al, lipid composition was analyzed in lipid rafts of human frontal brain cortex obtained between 3- and 18-h post-mortem, revealing that lipid rafts from AD brains exhibit aberrant lipid profiles compared to healthy brains.…”
Section: Lipids and Alzheimer’s Diseasementioning
confidence: 99%